Study on the Implementation of the Occupation Health and Safety Management and Monitoring Plan for the 5th Mekong Bridge at Paksun District, Bolikhamxay Province - SILIPHOKHA, Daophet; PHONHALATH, Keophousone; PHONGPHANYA, Phanthoudate; NHAOVARATH, Phetsakhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aims 1) to investigate the implementation of occupational health and safety management plan. 2) To analyse feasibility that may have impact risk and mitigation measures based on the risk principle impact assessment of Matrix model, 3) provide recommendation and prevention measures to the risks that might have toward to the health and safety of the workers on the 5th Mekong River bridge construction project at Paksan district Borikhamxay province. The researcher will investigate the project by analysing the work checklist, random observation of the events before the start and before the completion of the work of each day, interviewing the relevant people and witnesses of the event in 3 activities: (1) Wearing personal protection equipment in the formwork activities and taping concreting, (2) Construction activities of bridge, (3) Mechanical lifting activities above 2 meters that lead to the causes and effects that may occur for tools/machines, heat, scrap materials, fire spills, shocks, stairs, sharp materials, material transporting vehicles, dust, excavated holes, machines, cranes, crushers, mortar breakers, noise, vibration, materials. The finding of the study found that in the construction site of that project the worker have the risks and danger to health and safety, especially in the column construction activities which is the task that the source of electricity leakage, the land clearance activities for the road construction of the material transportation vehicles, material lifting activities which is one of the sources from the machine which indicated as a risk to encounter with the high level or unacceptable level. Therefore, there must be close monitored and the risk must be managed immediately.